Training as an updating teaching in the Medical Imaging and Radiophysics Degree - Félix González Pérez; Miriam Iglesias León (Medisur)
The development achieved in the health services demands the teachers Degree in Medical Imaging and Radiophysics' professional improvement. This demand requires professionalization in the action modes. Its updating in physical principles, human anatomy, radiological semiology, as well as its practical skills during education at work, are essential. The purpose of this paper is to present the conception of training as a form of teacher professionalization for content updating. The training structure for the teacher's professionalization in the Medical Imaging and Radiophysics Degree and the training pedagogical conception for its organization and application in this career's teachers at the Cienfuegos Medical Sciences University are presented.